Implementasi Layanan Informasi Berbantuan Video untuk Meningkatkan Aktualisasi Diri dalam Memanfaatkan Waktu Senggang Mahasiswa - Tri Kasda Akbar Setiawan; Neni Noviza (Scidacplus, 2025)
This study, titled Implementation of Video-Assisted Information Services to Enhance Self-Actualization in Utilizing Leisure Time Among UIN Raden Fatah Palembang Students, was motivated by the low awareness among final-semester students in using their leisure time productively. This study aims to describe self-actualization in the utilization of leisure time among 2021-cohort Guidance and Counseling (BPI) students of the Faculty of Da'wah and Communication, and to examine how video-assisted classical information services can enhance that self-actualization. A qualitative field-research approach was employed. Data were collected through observation, classical counseling sessions, and in-depth interviews with 15 final-semester BPI students, and were analyzed using Miles and Huberman's interactive model of data reduction, data display, and conclusion drawing/verification, with credibility established through source and technique triangulation. The findings show that video-assisted information services increased students' awareness of the importance of self-actualization and encouraged them to use their free time for beneficial activities such as independent learning, skill development, and building positive social relationships. The intervention was implemented in four stages across four sessions: needs identification and planning, service delivery, evaluation, and follow-up/reinforcement. These findings extend prior evidence on video-assisted counseling and leisure education by demonstrating their applicability to self-actualization among Indonesian university students.